Effect of Organic Amendment on the Physicochemical Characteristics of Tailings Dam Soil and Root Development of Tree Species, Fifteen Years After Planting - Mwanasomwe, Jacques Kilela; Langunu, Serge; Nkulu, Salvatora Nsenga; Shutcha, Mylor Ngoy; Colinet, Gilles (Frontiers in Soil Science, 2022)
Among mine wastes, tailings are known to have the largest environmental impact, as they have high concentrations of trace elements and are susceptible to wind dispersal and water erosion. A tree plantation trial was installed at Kipushi tailing (DR Congo) in order to mitigate the contaminant dispersal in the surrounding areas. Fifteen years later, the present study was conducted for the purpose of investigating the macronutrient and metal content in amended holes and assessing the performance of tree species through root behavior in the tailings dams. Results show elevated available P, K, Ca, and Mg concentration in the surface and amended layers which is higher than the unpolluted soil of the miombo woodland. Trace metals were manifold higher compared to the pedo-geochemical background of the region, with Cu and Co concentration tending to increase in the rich OM layers, while Zn, Cd, Pb, and As remained higher in tailings. Compared to the tailing layer, roots grew well in the amended layers, but few roots ranging from very fine to big from all the surviving species were able to grow beyond the amended layers indicating the possibility of tree survival on the tailings dams over many years. A. polyacantha and P. guajava are species that showed a higher quantity of roots in the unamended tailing layers. Leaves should be avoided for human or animal consumption, but as Cu, Zn, and Co concentration in guava-tree fruits was lower, there is no indication of hazards in case of their consumption. Therefore, the use of well-adapted tree species on the mixed up of the organic amendments with the uncontaminated topsoil seemed to be a good technique for the reclamation of larger polluted areas. Keywords: Trace metal, tailings, amendment, tree species, reclamation